The Effect Of Prone Position And Clapping On Secretion Exhaust And Oxygen Saturation In Patients With Obstructive Pulmonary Disease (Copd) At Kaimana Regional Hospital - Hariyono; Nancy Natalia Tho; Rani Ladjamali; Yuliana Torano; Sara Saludung; Siti Hadjar Maturbongs (Universitas STRADA Indonesia, 2025)
Disease lungs obstructive chronicle (COPD) is disease lungs Which marked by an increase resistance to air flow that is not completely reversible. Disease This is reason main morbidity and mortality which is chronic in the world. Every year many people suffer and die world because of this disease and its complications. This study aims to to determine the EFFECT OF PRONE POSITION AND CLAPPING ON SECRETION EXHAUST AND OXYGEN SATURATION Type study This is study quantitative with design study one group pre- posttest design. Sample on the process This using 7 Respondents Which suffer COPD. Analysis bivariate use test Wilcoxon Which aiming for know influence variable Prone Position and Clapping against secretion discharge and oxygen saturation. Results analysis bivariate use test Wilcoxon obtained mark p value = 0.025 then p value < 0.05 so H 0 rejected and H 1 accepted means there is The Effect of Prone Position on Breathing in Patients with Lung Disease Obstructive Chronicle (COPD). The prone position is a prone position that is recommended as an effort to overcome respiratory problems, namely reducing shortness of breath. The prone position is a position that is recommended as an effort to overcome respiratory problems, namely reducing shortness of breath. body client prone position where the head is lower than the shoulders, making the lung load more evenly distributed so that it can increase oxygen flow. This position is also believed to reduce lung pressure by intra-abdominal organs so that it will improve oxygenation and carbon dioxide clearance. Chest physiotherapy / Clapping is done by patting the chest or back to help loosen thick mucus in the lungs, so that it can come out easily through coughing. The conclusion of this study is that there is an effect of prone position and clapping on secretion discharge and oxygen saturation in patients with obstructive pulmonary disease (COPD).